BSN-I: the first in-depth photometric study of seven total-eclipse contact binary systems - Poro, A. (2025)
This is the first in-depth study of seven total-eclipse W Ursae Majoris-type contact binary systems using photometric light curves. The ground-based observations were conducted with four observatories in the Northern and Southern hemispheres. We also used the Transiting Exoplanet Survey Satellite for four target systems. We presented the analysis of orbital period variations of six systems and found that they display parabolic variations. The material transfer rates between the stars of the systems were calculated. Also, the results show that four systems have a long-term increase, while two have a long-term decrease in their orbital periods. We analysed light curves using the PHysics Of Eclipsing BinariEs PYTHON code and the Markov chain Monte Carlo algorithm to estimate different parameters of target systems and their uncertainties. Six of the target systems required the addition of a cold or hot star-spot. We estimated absolute parameters using the empirical relationship between the orbital period and the semimajor axis ( P−a). According to each component's effective temperature and mass, it was recognized that the studied systems are W subtype. We examined the dynamic stability of two targets, which were low mass ratio contact binary systems. We also showed the evolution of stars in the M−R and M−L diagrams. Finally, we showed that the hotter stars in contact systems have a temperature difference of less than ≈400 K compared to the Gaia Data Release 3 temperature report.